Problems Faced by People Living with HIV/AIDS in Makawanpur, Nepal - Moktan, Dhana Bahadur (Journal of Advanced Academic Research, 2023)
HIV/AIDS, in a sociological perspective, is a social problem that affects human beings and push towards immature death. It was reported in Nepal in 1988 for the first time, however, it is not so old disease, but at present, it has spread throughout the country as a wild fire. At present, it is estimated that about 75,000 people are infected with this infection (NCASC, 2012). People who infected with this infection are not discriminated or stigmatized until they exposed. If someone exposed that s/he is a victim of HIV/AIDS, people start to discriminate, stigmatize, and even exile from home and community blaming characterless or prostitute. Hence, this study was concentrated with the aim to find out the current problems faced by PLHAs i.e., female sex workers, homemakers, IDUs, transport workers, and MSWs in Makawapur district which is known as one of the twenty-six prone districts for the girls trafficking in Nepal. Required information was collected through in-depth interview, observation and group discussion based on their individual background, profession and problems. Disproportionate sampling design to draw 102 sample sizes with equal weight for male and female respondents was chosen. Snowball sampling to find the respondents was applied. Qualitative research was emphasized based on semi-structure and open-ended questions, however, quantitative research design also prioritized to analyze the data to make the study sounder.